Body weight dynamics and cardiovascular risk factors in climacteric women - A. A. Popov; N. V. Izmozherova; N. V. Tagiltseva; A. N. Andreev; O. Yu. Stryukova; E. V. Kozulina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To compare body weight (BW), lipid and carbohydrate metabolism dynamics in premenopausal, menopausal, and postmenopausal women. Material and methods. This cohort study included 573 volunteers aged 36-55 years. Mean follow-up period was 3,4 years. Anthropometric parameters, lipid and carbohydrate profiles, rates of arterial hypertension, coronary heart disease, chronic heart failure, myocardial infarction, and stroke were analyzed. All participants were divided into four groups: Group I – 104 women remaining in premenopause; Group II – 87 patients with developed menopause; Group III – 238 postmenopausal women; Group IV – 144 individuals in late postmenopause (>5 years). Results. Maximal mean BW, waist circumference (WC) and their increase were registered in Group II. During the follow-up, significant BW increase was observed in Groups II and IV. Three years alter, carbohydrate metabolism disturbances become significantly more frequent, especially in Group IV. Substantial BW and WC increase was observed in all groups, among participants with newly diagnosed carbohydrate metabolism disturbances; median three-year dynamics was 2 kg and 2 cm, respectively. Conclusion. Maximal BW and WC increase was observed during menopausal transition. In climacteric women, abdominal obesity was highly prevalent. Carbohydrate metabolism disturbance rate started to increase in menopause and continued to elevate in advanced age, being associated with BW increase (2 kg in 3 years).